Penerapan Metode At-Tartil Untuk Meningkatkan Kemampuan Membaca Al-Qur’an Di Tpq Nurul Huda Li’ulumil Qur’an Sooko Wringinanom Gresik - Abdul Munib; Muhammad Mahfud; Rahmat Rudianto (Jurnal Pendidikan Agama Islam Miazhar, 2022)
This research was carried out because there were many students at TPQ Nurul Huda Li'ulumil Qur'an Sooko Wringinanom Gresik who were not yet able to read the Koran properly and correctly. And the problems that researchers want to find answers to through this research are: 1) How effective is the At-Tartil method in improving the ability to read the Al-Qur'an at TPQ Nurul Huda Li'ulumil Qur'an Sooko Wringinanom Gresik? In this research, problem limitations were carried out, namely: 1) Search for information on the At-Tartil method of reading the Qur'an, 2) Search for information about the application of the At-Tartil method in improving the ability to read the Qur'an, 3) Search for information about application of the At-Tartil method in improving the ability to read the Koran. This research uses qualitative research methods with a descriptive approach. The results obtained are: 1) The at-Tartil method is a guide in learning to read the Qur'an directly (without spelling it) and incorporating/practicing refraction of tartil reading in accordance with the rules of ulumut tajwid and ulumul ghorib, 2) Application of the at-Tartil method -Tartil at TPQ Nurul Huda Li'ulumil Qur'an has been said to be good because the teaching and learning process at TPQ Nurul Huda Li'ulumil Qur'an has implemented the at-Tartil curriculum, most of which has been implemented, 3) Application of the at-Tartil method in reading the Koran at TPQ Nurul Huda Li'ulumil Qur'an is categorized as optimal, this can be seen from the test results of students in the marhalatul ula class which achieved an average score of 88%.